The Legal Position of the Churches in East Central Europe from 1945 to 1989 - Kozerska, Ewa (Lectures on East Central European Legal History, 2023)
After the end of hostilities, Central and Eastern Europe forcibly became a zone of Soviet influence. Local communist governments adopted the political and legal solutions of the USSR as their model. Under the assumed model of a secular state, they undertook anti-religious policies combined with indoctrination in the spirit of materialist philosophy. Despite the preservation of the appearance of religious freedoms under the façade constitutions, in reality, the legislation enacted and the actions of the administrative-police apparatus were aimed at destroying the organizational structures of the churches, reducing the authority of the clerical hierarchy and the Holy See, and regularly discouraging the faithful from religious practice. In the first years after the communist takeover, religious life was already successively subjected to the control of state bodies: the material heritage of the churches was appropriated, religious worship was licensed or paralyzed, and the clergy and faithful were persecuted. So-called patriot priests loyal to the regime were also effectively recruited, making it possible to break up church organizations and steer the faithful according to the prevailing ideology. The status of individual churches and religious associations was generally highly unstable under communist regimes, legally restricted, and above all dependent on the arbitrary will of the regime’s elite, whose overriding goal was to bring about the full secularization of societies. KEYWORDS: Church, religion, persecution, resistance, totalitarianism, communists, East Central Europe.